Effects of empagliflozin on exercise tolerance and left ventricular diastolic function in patients with heart failure with preserved ejection fraction and type 2 diabetes: a prospective single-center study - A. G. Ovchinnikov; A. A. Borisov; K. Yu. Zherebchikova; O. Yu. Ryabtseva; A. D. Gvozdeva; V. P. Masenko; F. T. Ageev; S. A. Boytsov (Российский кардиологический журнал, 2021)
Aim. To assess the effect of the sodium-glucose transport protein 2 inhibitor empagliflozin on exercise tolerance and left ventricular (LV) diastolic function in patients with heart failure with preserved ejection fraction (HFpEF) and type 2 diabetes (T2D).Material and methods. The present prospective, single-center, open-label study included 60 patients with HFpEF and T2D, who were assigned to groups receiving empagliflozin 10 mg/day. or previously taken hypoglycemic therapy (control group). The follow-up period lasted 24 weeks. All patients underwent a 6-minute walk test and rest and stress echocardiography at baseline and at the end of the study.Results. After 24 weeks. in the empagliflozin group there was an increase in the 6-minute walk test distance by 20 m (95% confidence interval (CI), from 7 to 33 m), a decrease in the early mitral inflow to mitral annulus relaxation velocities (E/e’) ratio by 1,8 (95% CI, from -2,4 to -1,2) and maximum left atrial volume by 2,6 (95% CI, from -4,4 to -0,8) ml/m2, as well as an increase in the diastolic reserve (mitral annulus relaxation velocity increment e’ during exercise increased from 2,2 (95% CI, 1,7 to 2,7) to 3,4 (95% CI, 2,4 to 4,2) cm/s; P<0,01 for all). There were no significant changes in the control group.Conclusion. In patients with HFpEF and T2D, empagliflozin improves exercise tolerance and LV diastolic function. Large-scale placebo-controlled randomized trials are required to prove these findings.